Edukasi Pengolahan Limbah Rumah Tangga dan Pelepah Kelapa Sawit menjadi Pupuk Kompos sebagai Upaya Pemberdayaan Masyarakat di Kepenghuluan Teluk Nilap Jaya, Kabupaten Rokan Hilir - Abdur Raihan Lubis; Ade Wira Armadana; Denny Simanjuntak; Firlin Ramadisha; Mifta Nabila Ulfa; Melisha Audi Putri; Muhammad Ramadhanu; Siti Aisah Nasution; Suci Khoirul Citra; Wulan Safiroh; Ali Asfar (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Teluk Nilap Jaya is a village within the Kubu Babussalam Sub-district of Rokan Hilir Regency, an area with abundant household organic waste and oil palm frond residue that is largely left unmanaged, generating both environmental problems and unrealized economic potential. Most residents still dispose of kitchen waste directly and rely on chemical fertilizer for their home gardens and smallholder plots. This community service activity was carried out by ten students of the Universitas Riau Kukerta Berdampak 2026 program to educate residents of Teluk Nilap Jaya on converting household organic waste and oil palm fronds into compost. The methods applied included lecture-based material delivery, interactive discussion, a live demonstration of the bucket-composting (ember) technique, and a question-and-answer evaluation session. Materials covered the benefits of organic compost, suitable waste materials, the role of rice-washing water, EM4 solution and brown sugar as decomposition accelerators, and the step-by-step composting procedure. The results showed that participants were enthusiastic, actively asked questions about composting materials and techniques, and gained a practical understanding of independent organic waste management. This activity is expected to reduce reliance on chemical fertilizer, minimize environmental pollution, and support the achievement of Village SDGs, particularly Goal 12 on responsible consumption and production and Goal 15 on the sustainable management of land ecosystems.